Analisis Perbaikan Sistem Kerja dengan Penerapan Metode 5R di Bengkel Bina Motor Service Jakarta Utara - Indra Rizki Pratama; Arif Dzulfikar; Busharmaidi; Fredy Sumasto; Isma Wulansari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The existence of quite tight competition in the automotive sector, especially workshops, makes customers more careful in choosing a quality workshop. The work system of the Bina Motor Services and Spare Parts workshop is classified as inefficient, because customers still wait quite a long time when carrying out motorbike services. Therefore, the aim of this research is to apply the 5Rs to create a more efficient and productive work system. The research method used is qualitative through observation and interviews to determine deficiencies in each stage of the 5S and the solutions. Implementation of 5R in the Bina Motor Services and Spare Parts workshop starts from the first stage, seiri, cleaning and disposing of unused items so that the work space becomes wider. The second stage, seiton, at this stage the activities carried out are grouping workshop equipment so that equipment is picked up more quickly by a mechanic. In the third stage, seiso, routine cleaning of workshop equipment from dust, dirt and oil is carried out. The fourth stage, seiketsu, there is a checklist so that the implementation of 5R is carried out continuously. In the final stage, shitsuke, there is a 5R poster put up to remind all Bina Motor Services and Spareparts workshop employees to always implement 5R in the workshop.